Easy Route to New Fused Dihydroisoquinoline-Naphthyridinone Frameworks - Shuvalov, Vladislav Yu.; Fisyuk, Alexander S. (Synthesis, 2023)
The reaction of 1-methyl-3,4-dihydroisoquinolines with azlactone, obtained from hippuric acid and phthalic anhydride, provided 2-(3-benzamido-4-oxo-6,7-dihydro-4H-pyrido[2,1-a]isoquinolin-2-yl)benzoic acids, which were converted into previously unknown dihydroisoquinoline-naphthyridinones by the action of hydrazine hydrate. Further reaction of the prepared naphthyridine-5,7-diones with POCl3 under various conditions led to the formation of 5-chloro-9,10-dihydro-7H-benzo[c]isoquinolino[1,2-g][1,7]naphthyridin-7-ones or 4,6-dichloro-2-(2-(2-methylprop-1-en-1-yl)phenyl)benzo[c][1,7]naphthyridines. It was also shown that the halogen atom in the C-5 position enters into a substitution reaction with primary and secondary amines.
Keywords: azlactone; benzo[c][1,7]naphthyridin-4(3H)-one; naphthyridine; рyrido[2,1-a]isoquinoline; pyridone-pyridol tautomerism